Evolution of Thermoviscoelastic Properties of Asphalt Mixtures with Oxidative Aging. Issue 1 (January 2014) - Morian, Nathan E.; Alavi, Mohammad Zia; Hajj, Elie Y.; Sebaaly, Peter E.
The uniaxial thermal stress and strain test (UTSST) provides a fundamental approach to characterize the thermoviscoelastic properties of asphalt mixtures and permits the pragmatic evaluation of changes in the stiffness and overall behavior of mixtures as a function of oxidative aging. The UTSST modulus was computed in the temperature domain with a linear viscoelastic constitutive equation from the measured thermally induced stress and strain. Five distinct stages, here named thermoviscoelastic properties, are identified from the modulus as a function of temperature: viscous softening, viscous-glassy transition, glassy hardening, crack initiation, and fracture stages. Through consideration of the thermoviscoelastic properties, marked differences in the aging process were noted in the evaluation of two binders and two aggregate sources over a range of air void levels. Typically, decreases in the viscous response of the mixtures as well as corresponding increases in both the stiffness and brittle behavior are presented as a function of aging. The evaluated behavior of the mixtures also provides a clearer understanding of the significant influence the air void level, or mixture density, has on the binder oxidation and overall mixture performance. The evaluation method provides definitive measures to monitor the progression of multiple aspects of the response of asphalt mixtures to thermally induced loading.